2003
DOI: 10.1007/s00464-002-9109-y
|View full text |Cite
|
Sign up to set email alerts
|

Palliation of pancreatic cancer using electrolytic ablation

Abstract: This experimental study suggested that electrolytic palliation of inoperable pancreatic cancer via the gastrointestinal tract is potentially safe. In patients, this treatment could be performed during endoscopic retrograde cholangiopancreatography and may have therapeutic advantages when compared to stenting or biliary bypass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 26 publications
(27 reference statements)
3
9
0
Order By: Relevance
“…However, by the 4 th post-operative day the serum amylase levels were not significantly (p > 0.05) different from the preoperative values. Previous experimental studies, reported by this group, have demonstrated that a transient hyperamylasemia is be caused by pancreatic duct cannulation alone, without electrolysis [35]. These experimental findings mirror clinical experience where diagnostic ERCP is associated with a significant increase in serum amylase concentration [9].…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…However, by the 4 th post-operative day the serum amylase levels were not significantly (p > 0.05) different from the preoperative values. Previous experimental studies, reported by this group, have demonstrated that a transient hyperamylasemia is be caused by pancreatic duct cannulation alone, without electrolysis [35]. These experimental findings mirror clinical experience where diagnostic ERCP is associated with a significant increase in serum amylase concentration [9].…”
Section: Discussionmentioning
confidence: 53%
“…Mean treatment time was 21 min (range: 18-22 min). The dose of 50 C was decided after analysis of both the data from a pilot study investigating the feasibility and safety of pancreatic electrolytic ablation and preexisting dose/volume data generated from previous studies into hepatic electrolytic ablation [32,34,35].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that per-ductal electrolytic ablation of the pancreas is both feasible and safe in the porcine model [12] . The results of this study not only support these previous fi ndings but also show that it is possible to endoscopically deliver an electrolytic ablative dose to the pancreas via the pancreatic duct, safely and with minimal short-or long-term morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, electrolysis has been shown to be safe in close proximity to vascular structures, which is not the case with other ablative techniques [11] . Previous experimental studies have shown that the delivery of an electrolytic dose to pancreatic tissue via a catheter inserted into the pancreatic duct is both feasible and safe in the short to long term [12] . In these studies, cannulation of the pancreatic duct was performed as an open procedure.…”
mentioning
confidence: 99%